Analisis Profitabilitas Bank Syariah Di Indonesia: Pendekatan Autoregressive Distributed Lag (ARDL) - Dewi, Fitri Kurnia; Sudarsono, Heri (Al-Mashrafiyah (Jurnal Ekonomi, Keuangan dan Perbankan Syariah), 2021)
This study aims to analyze the factors that affect the profitability of Islamic Commercial Banks in Indonesia. The dependent variable in this study is Return on Assets (ROA), while the independent variables include CAR, NPF, FDR, BOPO, DPK, mudharabah financing, murabahah financing, BI Rate, and inflation. The research period was from January 2015 to July 2020 using the Autoregressive Distributed Lag (ARDL) approach. This study found that in the short term NPF, FDR, BOPO, DPK, mudharabah financing, murabahah financing, and inflation are significant variables on profitability. Meanwhile, in the long term, the variables that are significant to profitability include CAR, BOPO, DPK, and BI Rate. Mudharabah and BOPO financing are the variables that have the biggest influence on profitability. Therefore, Islamic bank management needs to pay attention to the risk of financing using a profit-sharing scheme. In addition, management needs to maintain the level of bank efficiency by taking into account the use of funds to meet operational expense.